Implementasi Pasal 38 ayat (1) Undang-Undang Nomor 28 Tahun 2014 terhadap Ekspresi Budaya Tradisional di Kabupaten Sleman - Dyah Permata Budi Asri (Fakultas Hukum Universitas Islam Indonesia, 2016)
The issues in this research include first, how is the protection for the traditional-cultural expression recently done in Sleman Regency? Second, how is the attempt of Department of Culture and Tourism of Sleman Regency towards the legal protection to the traditional cultural expression in Sleman Regency? This is a juridical-empirical research by taking the primary data from the research field through observation and interview done to the informants (Department of Culture and Tourism of Sleman Regency and Ministry of Law and Human Rights, Regional Office of Special District of Yogyakarta) and supported with the secondary data. The result of this research concluded that first the protection given by the Local Government related to the obligation mandated by regulation of Copy Right is through the inventory, documentation and other activities regarding the cultural affair of speciality of Yogyakarta. Second, the further attempt to give the protection for the traditional culture expression in Sleman Regency is by making the database of culture based on the information system; thus, it can be accessed by all parties and as a media to promote the tourism in Sleman Regency.